2016
DOI: 10.1016/j.aquatox.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Parental dietary seleno-L-methionine exposure and resultant offspring developmental toxicity

Abstract: Selenium (Se) leaches into water from agricultural soils and from storage sites for coal fly ash. Se toxicity causes population and community level effects in fishes and birds. We used the laboratory aquarium model fish, Japanese medaka (Oryzias latipes), an asynchronous breeder, to determine aspects of uptake in adults and resultant developmental toxicity in their offspring. The superior imaging properties of the model enabled detailed descriptions of phenotypic alterations not commonly reported in the existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 81 publications
4
8
0
Order By: Relevance
“…Similar toxicity (i.e. pericardial edema) has been reported in a number of developmental Se exposure studies 2 38 40 41 , and Se-induced activation of the AhR2 signalling pathway may be involved in such toxicity. Both nrf2a and nrf2b have been demonstrated to participate in cross-talk with ahr2 in zebrafish 15 .…”
Section: Discussionsupporting
confidence: 76%
“…Similar toxicity (i.e. pericardial edema) has been reported in a number of developmental Se exposure studies 2 38 40 41 , and Se-induced activation of the AhR2 signalling pathway may be involved in such toxicity. Both nrf2a and nrf2b have been demonstrated to participate in cross-talk with ahr2 in zebrafish 15 .…”
Section: Discussionsupporting
confidence: 76%
“…The significance of this finding remains incompletely understood; selenium concentrations in fish testes are uncommonly reported in field studies and a recent analysis of such studies found that reported testes/milt concentrations are given little consideration relative to those of female fish muscle and ovary/egg tissue concentrations. 23 This issue likely reflects the prevailing theory that environmentally relevant selenium toxicity in early life stage fish occurs primarily due to selenium transfer from the maternal fish during vitellogenesis and embryonic exposure to this selenium during yolk resorption. 1 However, a recent study investigating the influence of parental selenium exposure on the occurrence of phenotypic abnormalities in F1 generation Japanese medaka ( Oryzias latipes ) reported paternal influence over some deformity categories (e.g., craniofacial) and that the highest rate of phenotypic alterations were found in the exposure group in which both maternal and paternal fish were dietarily exposed to seleno-Lmethionine.…”
Section: Discussionmentioning
confidence: 99%
“…Tadpoles have a chondrified skeleton during early premetamorphosis stages with ossification generally starting in most species during late premetamorphosis (developmental stage sampled in this experiment). Previous studies have reported spinal and craniofacial deformities in tadpoles and fish exposed to Se, which may relate to the Se accumulations in these structures. ,, A recent study found that exposure to selenomethionine altered the expression of genes involved in the skeletogenesis of fish during early development . The study found a decreased expression of melatonin receptor ( Mtr ) in exposed fish (10–500 μM selenomethionine) and suggests that Se-induced skeletal deformities are caused by a blockage or inhibition of melatonin.…”
Section: Resultsmentioning
confidence: 97%